1980
DOI: 10.1159/000212390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Voluntary Wheel Exercise on Male and Female Wistar Rats

Abstract: Male and female Wistar rats (n = 140) age 1.5 months were maintained in either wheel-cage units or cage units for their entire life span. Voluntary wheel exercise significantly increased the mean longevity of both male and female rats compared with that of control rats. Between and within groups, growth duration was positively related to longevity, and growth rate was negatively related to longevity. These factors may explain differences in longevity between exercise and control groups and differences in longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 16 publications
(26 reference statements)
4
69
0
2
Order By: Relevance
“…Indeed, it has been shown that despite similar mitochondrial density, LCRs have reduced mitochondrial respiratory capacity in skeletal muscle compared to HCRs [33]. This is consistent with the finding, that skeletal muscle from obese subjects or from type 2 diabetic patients show reduced mitochondrial oxidative capacity [20,23,25,34]. A novel finding from the present study was that LCRs become promptly fatigued during maximal isometric muscle stimulation (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, it has been shown that despite similar mitochondrial density, LCRs have reduced mitochondrial respiratory capacity in skeletal muscle compared to HCRs [33]. This is consistent with the finding, that skeletal muscle from obese subjects or from type 2 diabetic patients show reduced mitochondrial oxidative capacity [20,23,25,34]. A novel finding from the present study was that LCRs become promptly fatigued during maximal isometric muscle stimulation (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Modified from Edington et al 1972. More recently, two studies on specific-pathogen-free male Long-Evans and Wistar rats confirmed that exercise results in improved survival but does not improve maximal lifespan Goodrick 1980). In Goodrick's study the rats started the intervention at an age of 1.5 months and in Holloszy's at the age of 9 months.…”
Section: Physical Activitymentioning
confidence: 99%
“…The hypoactivity observed in old ham sters in this study has also been reported for old rats allowed access to running wheels [Goodrick, 1980], Both the pattern and in tensity of spontaneous running were mark edly affected. Individual bouts of exercise were shorter, pauses were longer and speed was significantly reduced with age.…”
Section: Discussionsupporting
confidence: 85%
“…For example, vigorous exercise training in humans and other mammals has been shown to increase cognitive capacity (Suominen-Troyer et al, 1986), locomotor performance (Skalicky et al, 1996), motor coordination (Dorner et al, 1997), antioxidant capacity (Gündüz et al, 2004;Kayani et al, 2008), resistance to cellular oxidative damage (Radák et al, 1999), immune function (Utsuyama et al, 1996) and lifespan (Paffenbarger et al, 1993;Lee and Paffenbarger, 2000). Alternatively, prolonged sedentarism in otherwise active mammal species can decrease running capacity (Swallow et al, 1998), lower the maximum rate of O 2 uptake (Overton et al, 1986;MacNeil and Hoffman-Goetz, 1993), increase body mass (Mlekusch et al, 1996;Swallow et al, 1998) and decrease lifespan (Goodrick, 1980;Holloszy, 1988;Franco et al, 2005;Bronikowski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%